Federalism and the dictatorship of power in Russia - Stoli͡arov, M. V. (Mikhail Venediktovich), 1945- (Routledge studies of societies in transition, 2003)
This work explores the historical traditions and distinctive features of modern Russian federalism. It reviews the state of affairs in today's Russia as it strives to become a federal democracy securing the rights and liberties of its citizens.